2003
DOI: 10.1080/030794502100007187
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus identified as cause of disease in young geese

Abstract: The pathology, epizootiology and aetiology of a specific disease of young geese, which has been seen in Hungary for more than three decades, were investigated. The disease was characterised by splenitis and hepatitis with miliary necrotic foci during the acute phase, and epicarditis, arthritis and tenosynovitis during the subacute/chronic phase. Clinical signs usually appeared at 2 to 3 weeks of age and persisted for 3 to 6 weeks. From different organs of the affected birds, a reovirus was isolated in embryona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…In 1972, Walke et al confirmed the virus as a “reovirus” [4]. Researchers subsequently identified ARV infection in South Africa, France, Israel, Italy, China, and many other countries [57]. In 1997, the main Muscovy duck breeding region in China was affected by an outbreak of duck reovirus (DRV) disease, which resulted in white spots on the liver.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1972, Walke et al confirmed the virus as a “reovirus” [4]. Researchers subsequently identified ARV infection in South Africa, France, Israel, Italy, China, and many other countries [57]. In 1997, the main Muscovy duck breeding region in China was affected by an outbreak of duck reovirus (DRV) disease, which resulted in white spots on the liver.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that GRV can cause viral arthritis in geese, and infected geese often exhibited spleen inflammation, while those with subacute or chronic onset showed pericarditis, arthritis, and/or tenosynovitis [7]. The GRV induced clinical symptoms appeared at 2–3 weeks of age, and the disease course lasted 3–6 weeks [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARV affected poultry flocks commonly suffer from viral arthritis/tenosynovitis, enteric disease, immunosuppression, runting-stunting syndrome, and malabsorption syndrome (Sterner et al, 1989; van der Heide, 2000). Most domestic avian species are susceptible to ARV infections, such as broiler breeders (Ide and Dewitt, 1979), layer breeders (De Gussem et al, 2010), broilers (Howell and Walker, 1972), goose (Bezerra et al, 2012; Palya et al, 2003), turkey (Giangaspero et al, 1997; Taber et al, 1976), duck (Baroni et al, 1980; Petek et al, 1973; Rey et al, 1999), pigeon (Vindevogel et al, 1982), and quail(Guy et al, 1987; Magee et al, 1993; Ritter et al, 1986). However, the meat-type chickens are well documented species that are more susceptible to the viral arthritis/tenosynovitis caused by ARV than other avian species (De Gussem et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Avian orthoreovirus (ARV) is an important etiological agent that can cause several economically devastating diseases in a variety of domestic and wild birds, including chickens1, turkeys2, Muscovy ducks3, Pekin ducks4, geese56, wild mallard ducks7, pigeons8, psittacine birds9 and other wild birds. In waterfowl species, causative ARVs were first isolated in France in 1972 from Muscovy ducks, historically termed Muscovy duck reovirus (MDRV)3 and emerged in China in 199710.…”
mentioning
confidence: 99%